The Structure of Academic Self-Concept: A Methodological Review and Empirical Illustration of Central Models. (February 2021) - Arens, A. Katrin; Jansen, Malte; Preckel, Franzis; Schmidt, Isabelle; Brunner, Martin
The structure of academic self-concept (ASC) is assumed to be multidimensional and hierarchical. This methodological review considers the most central models depicting the structure of ASC: a higher-order factor model, the Marsh/Shavelson model, the nested Marsh/Shavelson model, a bifactor representation based on exploratory structural equation modeling, and a first-order factor model. We elaborate on how these models represent the theoretical assumptions on the structure of ASC and outline their inherent psychometric properties. We analyzed these models using a data set of German 10th - grade students (N = 1, 232) including a wide range of domain-specific ASCs as well as general ASC. The correlations among ASCs and between ASCs and academic achievement varied depending on the structural model used. We conclude with discussing recommendations for research purposes and advantages and limitations of each ASC model. Our approach may also guide research on other affective or motivational constructs (e.g., academic anxiety or interest).